Polypharmacy as a risk factor for depressive symptoms in geriatric patients: an observational, cross-sectional study - Spandel, Leszek; Jośko-Ochojska, Jadwiga; Batko-Szwaczka, Agnieszka (Ars Pharmaceutica (Internet), 2016)
Aim: The aim of this study was to investigate the correlation between polypharmacy and depressive symptoms in hospitalized adults aged over 65 years. Patients and methods: We obtained medical history and current treatment data from clinical records. We used the Abbreviated Mental Test Score (AMTS) to exclude patients with dementia. The Geriatric Depression Scale (GDS) was used assess depressive symptoms. Pearson and Spearman coefficients were used to determine the relationship between variables. Results: A total of 206 individuals were included. The average number of medications taken by the individuals was 6.9 ± 2.7 and the average GDS score was 4.9 ± 3.4 points. Depressive symptoms (GDS score >5 points) were observed in 68 (33.0%) individuals. GDS score positively correlated with the number of medications used (R = 0.74; P = 0.0001), the number of chronic conditions (R = 0.78; P = 0.001), and pain complaints (Z = 7.94; P = 0.0001). A significant association between GDS score and the use of the following medications was observed: statins, cytostatic agents, corticosteroids, benzodiazepines, cardiac glycosides, non-steroidal anti-inflammatory drugs, muscle relaxants, non-psychotropic drugs with anticholinergic properties, and centrally acting analgesics (all P < 0.05). Conclusions: Our study indicates that polypharmacy is positively correlated with the presence of depressive symptoms in geriatric patients. We identified a number of medications associated with a higher prevalence of depressive symptoms, however these relationships require further examination.